Exercise-induced muscle damage is not attenuated by beta-hydroxy-beta-methylbutyrate and alpha-ketoisocaproic acid supplementation. - Nunan, D; Howatson, G; van Someren, K (2010)
The purpose of this study was to examine the effects of combined oral beta-hydroxy-beta-methylbutyrate (HMB) and alpha-ketoisocaproic acid (KIC) supplementation on indices of exercise-induced muscle damage (EIMD) after an acute bout of eccentric-biased exercise. Fourteen male subjects were allocated to 2 groups: a placebo group (3 g.d corn flour, N = 7) or an HMB + KIC group (3 g.d HMB and 0.3 g.d KIC, N = 7). Supplementation commenced 11 days before a 40-minute bout of downhill running and continued for 3 days post-exercise. Delayed-onset muscle soreness, mid-thigh girth, knee extensor range of motion, serum creatine kinase (CK) activity, and isometric and concentric torque were assessed pre-exercise and at 24, 48, and 72 hours post-exercise. Delayed-onset muscle soreness, CK activity, and isometric and concentric torque all changed over the 72-hour period (p < 0.05); however, HMB + KIC had no significant effect on any of the indices of muscle damage. Although 14 days HMB and KIC supplementation did not attenuate indices of EIMD after an acute bout of unaccustomed eccentric-biased exercise, there was a trend for a more rapid rate of recovery in isometric and isokinetic muscle function. beta-hydroxy-beta-methylbutyrate and KIC may therefore provide limited benefit in the recovery of muscle function after EIMD in untrained subjects or after unaccustomed exercise.